Preparation and Characterization of Lanthanum (III) Selective Electrode Based on 1,10-Diaza-4,7,13,16-Tetraoxacyclooctadecane-N,N’-Diacetic Acid as an Ionophore - Suyanta, Suyanta; I.R, Susanto; Buchari, Buchari; Noviandri, Indra (Jurnal Pendidikan Matematika dan Sains, 2012)
The preparation and characterization of lanthanum (III) ion selective electrode based on the 1,10-diaza-4,7,13,16-tetraoxacyclooctadecane-N,N’-diacetic acid as ionophore was studied. The electrode was prepared with an inner solution system in a membrane composition that contained active DACDA ionophore, the anionic side of KTCPB, the plasticizer of NPOE and a PVC matrix support. The good response was obtained with a slope of 19.53 +- 1.62 mV/decade and a good correlation between potential and lanthanum (III) concentration. Electrode could response with a detection limit of 3.92x10^-6 M and range measurement between 10^-5 M to 10^-1M. Electrode is steady at pH 4-9 and the best condition of inner solution concentration at 10^-3 M. Response time was 27.1 seconds and their life time was 50 day.<br style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px;" /><br style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px;" /><em style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px;">Kata kunci: lanthanum ion-selective-electrode, PVC membrane, 1,10-diaza-4,7,13,16-tetraoxacyclooctadecane-N,N’-diacetic acid